Investigation of financial performance of rural cooperatives network of Guilan province after implementation of centralized agricultural purchase and sale plan - Alireza Sahebdel Ali Jahani; Mohammad Kavoosi Kalashami; Gholamreza Mahfouzi (تعاون و کشاورزی, 2020)
Expansions of distribution and sales networks as well as diversification of domestic suppliers and diversified supply methods and also, price fluctuations make purchasing process complex and cost management necessary. The main purpose of this study is to investigate the financial performance of rural cooperatives network of Guilan province after implementation of centralized agricultural purchase and sale plan. This research is applied in terms of purpose, descriptive-analytical in terms of research method and the documentary method of data collection is also used. In order to fulfill the research objectives, the financial information of 91 cooperative units was studied and analyzed over a seven-year period from 2011 to 2016. The research methodology is a post-event type (using past information). Due to the panel nature of the data, panel regression and Eviews software were used for statistical analysis. The results showed that the ratio of debt to asset or financial leverage, size of cooperative, cooperative loans, and dummy variable for mentioned plan implementation had an indirect (negative) effect on cooperative ROE during the understudy period. Meanwhile, the negative effect of leverage, size and loans was statistically significant at the five, one and one percent levels, respectively. Also, during the study period, cooperative capital, cooperative sales, cooperative current ratio and cooperative futures ratio had a direct (positive) and statistically significant effect on ROE at one percent level.